2001
DOI: 10.4049/jimmunol.167.8.4137
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-17F, a Novel Cytokine Selectively Expressed in Activated T Cells and Monocytes, Regulates Angiogenesis and Endothelial Cell Cytokine Production

Abstract: A novel secreted cytokine, termed IL-17F, was cloned using nested RACE PCR. This cytokine bears homology to IL-17. IL-17F was expressed only in activated CD4+ T cells and activated monocytes. Recombinant human IL-17F did not stimulate the proliferation of hematopoietic progenitors or the migration of mature leukocytes. However, it markedly inhibited the angiogenesis of human endothelial cells and induced endothelial cells to produce IL-2, TGF-β, and monocyte chemoattractant protein-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
252
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(261 citation statements)
references
References 32 publications
3
252
1
5
Order By: Relevance
“…To examine if SCUBE1 could have a similar role, we tested whether SCUBE proteins, like LTBPs, are capable of binding growth factors or cytokines. Flag.SCUBE1 was co-expressed individually with PDGF-D, IL-8, or IL-17F, all of which are expressed in or have functions in EC (27,28,47,48). In our primary studies, Flag-.SCUBE1 proteins were capable of forming stable complexes with PDGF-D and IL-17F but not with IL-8 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…To examine if SCUBE1 could have a similar role, we tested whether SCUBE proteins, like LTBPs, are capable of binding growth factors or cytokines. Flag.SCUBE1 was co-expressed individually with PDGF-D, IL-8, or IL-17F, all of which are expressed in or have functions in EC (27,28,47,48). In our primary studies, Flag-.SCUBE1 proteins were capable of forming stable complexes with PDGF-D and IL-17F but not with IL-8 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The first reported study of IL-17F activity showed that IL-17F induces TGF-␤, lymphotoxin ␤, and IL-2 from endothelial cells in vitro (20). A subsequent study demonstrated that IL-17F can also induce G-CSF and CXCL1 from primary human epithelial cells (11).…”
mentioning
confidence: 99%
“…First cloned in 1993 from a murine cDNA library and known originally as CTLA-8 [23,24], IL-17A is a member of a family of IL-17 cytokines (IL-17A-F [25][26][27][28][29]) which are structurally homologous to each other and to a gene in the herpesvirus saimiri [23,30]. It was described initially as a product of activated and memory CD4 + T cells [23,30,30,31] but it is now known that the production of IL-17A is more ubiquitous and has been demonstrated in gd T cells [32], CD8 + memory T cells [31,33], eosinophils [34], neutrophils [31] and monocytes [35].…”
Section: Il-17mentioning
confidence: 99%